A break in parental interaction does not affect the temporal dependency of infant social engagement, but disrupts non-social engagement. Issue 1 (December 2018) - Mattson, Whitney; Messinger, Daniel; Gangi, Devon; Myers, Nicholas
Abstract Infant looking patterns during interaction offer an early window into social and nonsocial engagement. Recent evidence indicates that infant looks exhibit temporal dependency—one look duration predicts the next look duration. It is unknown, however, whether temporal dependency emerges as infants structure their own looking or whether it is influenced by interaction. We examined whether a perturbation of social interaction affected temporal dependency. Using the Face-to-Face/Still-Face procedure, we compared temporal dependency during parental interaction (the Face-to-Face & Reunion episodes) to parental non-responsiveness (the Still-Face episode). Overall, the durations of successive infant looks were predictable; past behavior constrained current behavior. The duration of one look at the parent (Face Look ) predicted the duration of the nextFace Look . Likewise, the duration of a look at any place that was not the parent's face (Away Look ) predicted the duration of the nextAway Look . The temporal dependency ofFace Looks (social engagement) was unaffected by the Still-Face perturbation, but the temporal dependency ofAway Looks (nonsocial engagement) declined during the Still-Face. Infant temporal structuring of engagement during social looking is not dependent on parental interaction while the disruption of interaction affects infants' structuring of their own non-social engagement.